NINGEN KANKEI TOKOH UTAMA DALAM NOVEL SHINSHO TAIKOKI BUKU I KARYA EIJI YOSHIKAWA TINJAUAN SOSIOLOGI SASTRA - Wahyu Dwi Hartadi, Kadek (Humanis; Volume 1. No. 2. Desember 2012)
Society consists of several individuals who interact and relate to one another. In his daily life, interactions prompted the mutual influence, mutual aid also appear even competing. In Japanese society, there is a term that describes the relationship between individuals that occurred in the middle of the scope of the social life of the community, which became known as ningen kankei. According Yonenama, ningen kankei is the relationship between the human psyche, human relations that are common in the community of Japan.On a literary work, a lot of the concept of ningen kankei displayed in it. one of them is Eiji Yoshikawa's work, Shinsho Taikoki. Shinsho Taikoki is the work of legendary novelist Eiji Yoshikawa. This novel tells the story of Japanese history displayed through the spirit and tenacity of life experienced by Toyotomi Hideyoshi figures from small to manage a subordinate samurai Nobunaga Oda. Through the life of Toyotomi Hideyoshi is then explained various concepts of interpersonal relationships in Japanese society.
Keywords: society, social life of the community ,ningen kankei